ANALISIS HUKUM PERLINDUNGAN MEREK ASING TERHADAP TINDAKAN PENDAFTARAN SECARA ITIKAD TIDAK BAIK (STUDI PUTUSAN NO. 108/PK/Pdt.Sus/2011) - ANDY HORISON (PREMISE LAW JURNAL, 2015)
A brand is an important element which is adhered to goods and services. brand is a product identity that distinguishes one product with another product. Generally, it is a brand and not a product which makes goods interested and its price high. The more well-known a brand is, the more it is interested by people. However, its fame also causes it to be the violating target, and what usually occurs is bad faith in registering the brand. So the legal arrangements regarding the protection of the brand is the most important part of the law of the brand. This condition has made the researcher conduct a research on the protection of foreign brands toward bad faith in registering a brand. Keywords: Brand Protection, Brand Registration, Bad Faith